Pengaruh latihan split squat jump, jump to box dan kelentukan terhadap kemampuan tendangan tengkong bailian wushu - Firman, Firman; Barlian, Eri; Syahrastani, Syahrastani; Irawan, Roma (Jurnal Konseling dan Pendidikan, 2024)
This research highlights the strategic role of sports in improving the quality of human resources, focusing on Wushu as a branch of achievement. There is a dominant attack technique, Tengkong Bailian, which requires strength, speed, and precision. Plyometric exercises, such as Split Squat Jump and Jump To Box, are recognized as methods to increase muscle power. Flexibility is also considered crucial in sports activities, and the technical development of Wushu athletes requires the integration of plyometric training with a focus on strength, speed, and flexibility. This study tried to reveal the difference in the influence between the two plyometric exercise methods on the ability of Tengkong Bailian, taking into account the degree of flexibility. Results showed that both methods were effective, with Split Squat Jump superior at high flex, and Jump To Box more effective at low flex. The implication is that the integration of both training methods can promote optimal results in coaching Wushu athletes, with emphasis on individual characteristics and degree of flexibility. These findings provide guidance for Wushu trainers to develop effective exercise programs